L-Arginine in Nutrition: Multiple Beneficial Effects in the Etiopathology of Diabetes - Stancic, Ana; Korac, Aleksandra; Buzadzic, Biljana; Otasevic, Vesna; Jankovic, Aleksandra; Vucetic, Milica; Korac, Bato (Journal of Nutritional Therapeutics, 2013)
L-arginine is a nutritionally important amino acid that controls a wide spectrum of cellular functions and physiological processes, acting by itself or through its various metabolites. There are several factors that determine overall L-arginine homeostasis: dietary supplementation, endogenous de novo synthesis, whole-body protein turnover and its extensive metabolism. The destiny of L-arginine is determined by the complex network of enzymes and pathways differentially expressed according to health and disease status. Diabetes is characterized by reduced concentrations of L-arginine in plasma and many tissues, and failure of its metabolic effects. Emerging data suggest that oral supplementation of L-arginine exerts multiple beneficial effects on the complex etiological and pathophysiological basis of diabetes including: i) β-cell function and mass and ii) obesity and peripheral insulin resistance. This review emphasizes important aspects of L-arginine action which classifies this amino acid as a promising therapeutic approach in the treatment of diabetes.